Preliminary Study of Glucose Removal Using Biosorbents from Ananas comosus Leaves - Nurul Fathira Anisa, Jimali; Chan, Yen San; Angela, Siner (Trans Tech Publications Ltd, Switzerland, 2022)
The usefulness of Ananas comosus (pineapple) is not limited its fruits. This study aims to explore the removal of glucose, which are present in clinical waste by pineapple leaf biosorbents derived through three pre-treatment methods. Particle size analysis showed the smallest particle were from the steam pre-treated biosorbents and largest particles were from the 5% alkali pre-treated biosorbents. Fourier Transform Infrared Spectroscopy showed that lignin, hemicellulose, and cellulose remained unchanged in both the used and unused biosorbents. Despite the large particle size of the alkali pre-treated biosorbents, up to 70% of glucose was removed which might be due the improvement of the interfacial adhesion during the alkali treatment process.